PENGARUH KESADARAN MEREK, KESAN KUALITAS DAN ASOSIASI MEREK TERHADAP PENERIMAAN PERLUASAN MEREK DETTOL MELALUILOYALITAS MEREK - WIJAYA PUTRA, EGGIE (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract:This study aims to analyze and discuss the effects of brand awarenes, percieved of quality andbrand associations on brand extension acceptance with brand loyalty as the intervening variabel. The type of this research is quantitative. The sampling technique that used was accidental sampling with sample size of 165 respondents. Data analysis techniques using PASW Statistics 18 software and AMOS 21. Result of the research shows that significant effect betwen Brand awareness, percieved of quality and brand associations on brand loyalty.Brand awareness, percieved of quality and brand associations on brand extension acceptance.Brand loyalty on brand extension acceptanceand brand awareness, percieved of quality and brand associationson brand extension acceptancewith brand loyalty as the intervening variabelin product of company Reckitt Benckiser Indonesia (RBI) with their superior brand : Dettol. Keywords: brand awareness, percieved of quality, brand associations, brand loyalty and brand extension acceptance.